Corporate Political Connections and Favorable Environmental Regulatory Enforcement - Heitz, Amanda; Wang, Youan; Wang, Zigan (Management Science, 2023)
We examine whether the Environmental Protection Agency (EPA) uniformly enforces the Clean Air Act for politically connected and unconnected firms using a close election setting. We find no difference in regulated pollutant emissions or EPA investigations between the two groups, although connected firms experience less regulatory enforcement and lower penalties. These results are more pronounced for firms connected to politicians capable of influencing regulatory bureaucrats and for connected firms that are more important to their supported politicians. Taken together, our results show that campaign contributions can indirectly benefit firms by way of reduced environmental regulatory enforcement and penalties. This paper was accepted by Colin Mayer for the Special Issue of Management Science: Business and Climate Change. Supplemental Material: The data files and online appendix are available at https://doi.org/10.1287/mnsc.2020.3931 .